Preparation method of self-aggregation type corrosion inhibitor for oil and gas production and transportation based on heterocyclic substitution

CN122588562BActive Publication Date: 2026-10-09BETTER OILFIELD TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611090116.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-09
Estimated Expiration
2046-07-22

AI Technical Summary

Technical Problem

目前管道缓蚀主要采用均匀添加法、内防腐涂层技术或阴极保护法;在缓蚀剂分子设计上,多采用单一结构的有机化合物,依靠极性基团在金属表面进行物理吸附或弱化学吸附;传统缓蚀剂分子结构单一,与金属表面结合力弱,覆盖取向无规导致致密性差,在高流速或高温油气环境中容易发生脱附失效,长效性差;

Benefits of technology

基于本发明中特定摩尔配比下胺醛缩合形成的含氮硫杂环取代基团及亚甲基桥连结构,增加了分子中有效配位位点,使得缓蚀剂分子与金属表面形成高强度键合;结合本发明中所述的聚甲基丙烯酸包覆层以及表面羧基化导电炭黑,通过上述包覆层与碳黑在微电场作用下的协同物理化学属性,驱动微胶囊向阳极区域发生定向迁移,进而实现缓蚀剂在阳极腐蚀区的局部富集。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of pipeline corrosion prevention and fine chemical industry, in particular to a preparation method of a self-aggregation type oil and gas extraction and transportation special corrosion inhibitor based on heterocyclic substitution; the method comprises the following steps: heterocyclic corrosion inhibitor molecule preparation, zinc ion cross-linking and plugging response mesoporous nano container preparation, and microcapsule in-situ polymerization assembly; the application enhances the coordination adsorption of the corrosion inhibitor and a metal surface by introducing a heterocyclic substituent group, realizes on-demand release triggered by iron ions by cross-linking and closing the mesoporous structure with zinc ions and ethylenediaminetetraacetic acid, and realizes directional aggregation of the carboxylated conductive carbon black and the polymer coating layer to the anode corrosion area under the response of a micro electric field and pH; the application overcomes the defects of traditional corrosion inhibitors, such as easy desorption failure under high temperature and high flow rate, inability to accurately and directionally enrich, and no selective addition, and realizes local high-concentration enrichment of the corrosion inhibitor, on-demand release in response, and long-acting corrosion prevention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of pipeline corrosion prevention and fine chemical technology, specifically to a method for preparing a self-aggregating corrosion inhibitor for oil and gas production and transportation based on heterocyclic substitution. Background Technology

[0002] Corrosion of metal pipelines is a long-standing technical problem in the industrial field. Traditional corrosion inhibition technology mainly achieves overall protection by uniformly adding corrosion inhibitors to the fluid; in recent years, novel corrosion inhibitors with environmental responsive characteristics have become a research hotspot, aiming to improve the distribution of the agent in pipelines; Currently, pipeline corrosion inhibition mainly employs uniform addition, internal anti-corrosion coating technology, or cathodic protection. In terms of corrosion inhibitor molecular design, most use organic compounds with a single structure, relying on polar groups for physical adsorption or weak chemical adsorption on the metal surface. Traditional corrosion inhibitors have a single molecular structure, weak bonding force with the metal surface, and random coverage orientation leading to poor compactness. They are prone to desorption failure in high flow rate or high temperature oil and gas environments, resulting in poor long-term effectiveness. Existing technologies cannot achieve the directional aggregation of corrosion inhibitors to the corroded area, resulting in insufficient inhibitor concentration in the severely corroded anodic area and excessive consumption of the inhibitor in non-corroded areas; existing responsive corrosion inhibitors lack a deep response to the local microenvironment and cannot achieve dynamic matching between the inhibitor release rate and the actual degree of corrosion. Summary of the Invention

[0003] The purpose of this invention is to provide a method for preparing a self-aggregating corrosion inhibitor specifically for oil and gas production and transportation based on heterocyclic substitution. Existing pipeline corrosion inhibition technologies are prone to desorption failure in high-temperature and high-flow-rate environments, and have shortcomings in the directional aggregation of corrosion inhibitors into the corrosion zone. This invention provides a preparation method that can achieve local enrichment of corrosion inhibitors in the anodic region, dynamically match the actual corrosion degree, and release them on demand. The specific technical solution is as follows: A method for preparing a self-aggregating corrosion inhibitor for oil and gas production and transportation based on heterocyclic substitution, characterized by comprising the following steps: Heterocyclic corrosion inhibitor molecules were prepared by amine-aldehyde condensation reaction of diethylenetriamine, 2-aminothiazole and formaldehyde under acidic conditions, wherein the molar ratio of diethylenetriamine, 2-aminothiazole and formaldehyde was 1:(1.8-2.2):(1.8-2.2). Mesoporous silica nanocontainers with zinc ion crosslinking on their surfaces were prepared using the aforementioned heterocyclic corrosion inhibitor molecules, ethylenediaminetetraacetic acid-silane coupling agent, and zinc salt solution. The nanocontainers and surface carboxylated conductive carbon black were ultrasonically dispersed in an aqueous solution containing methacrylic acid monomer, crosslinking agent, and initiator at a mass ratio of (2.5-3.5):1 to form an aqueous phase. The mass of methacrylic acid monomer was 100 parts, the crosslinking agent was 2-10 parts, the initiator was 0.5-2 parts, and the total mass of the nanocontainers and surface carboxylated conductive carbon black was 35-45 parts. The aqueous phase is added dropwise to the oil phase containing the emulsifier, with a volume ratio of aqueous phase to oil phase of 1:(2-5), and shearing is performed to form a reverse microemulsion. After deoxygenation, the temperature is raised to carry out an in-situ free radical polymerization reaction to form a polymethyl methacrylate coating layer on the surface of the nanocontainer. After the reaction is completed, demulsification, centrifugation washing and freeze drying are performed in sequence to obtain the corrosion inhibitor.

[0004] Preferably, the in-situ free radical polymerization reaction is carried out at a temperature of 60-70°C for 3-5 hours.

[0005] Preferably, the crosslinking agent is N,N-methylenebisacrylamide; the initiator is potassium persulfate; the emulsifier is sorbitan monooleate; and the oil phase is cyclohexane.

[0006] Preferably, the mesoporous silica nanocontainer with zinc ions crosslinked on its surface is an MCM-41 type mesoporous silica with a pore size of 2.2-2.8 nm; and the surface carboxylated conductive carbon black has a particle size of 180-220 nm.

[0007] Preferably, the preparation of the mesoporous silica nanocontainer with zinc ions cross-linked on its surface includes the following steps: Step 1: Disperse mesoporous silica in a methanol solution containing heterocyclic corrosion inhibitor molecules, wherein the mass ratio of mesoporous silica to heterocyclic corrosion inhibitor molecules is 1:(0.5-2), stir to carry out physical adsorption loading, and collect by centrifugation to obtain supported mesoporous silica. Step 2: Under nitrogen protection, the supported mesoporous silica is dispersed in anhydrous toluene, and ethylenediaminetetraacetic acid-silane coupling agent is added, wherein the mass ratio of the dried supported mesoporous silica to the ethylenediaminetetraacetic acid-silane coupling agent is 1:(0.5-1.5). The mixture is heated under reflux to complete the surface grafting and obtain grafted mesoporous silica. Step 3: Disperse the grafted mesoporous silica in an aqueous solution containing zinc sulfate, wherein the mass ratio of grafted mesoporous silica to zinc sulfate is 1:(1-3), stir for crosslinking, centrifuge, wash and freeze dry to obtain mesoporous silica nanocontainers with zinc ions crosslinked on the surface.

[0008] Preferably, the preparation steps of the ethylenediaminetetraacetic acid-silane coupling agent are as follows: under nitrogen protection, ethylenediaminetetraacetic acid dianhydride and 3-aminopropyltriethoxysilane are added to N,N-dimethylformamide solvent at a molar ratio of 1:(2-2.5), and the mixture is stirred and reacted at 40-60°C for 12-24 hours. After the reaction is completed, the mixture is washed and vacuum dried to obtain the ethylenediaminetetraacetic acid-silane coupling agent.

[0009] The beneficial effects of this invention are as follows: Based on the nitrogen- and sulfur-containing heterocyclic substituent groups and methylene bridging structures formed by amine-aldehyde condensation under specific molar ratios in this invention, the effective coordination sites in the molecule are increased, enabling the corrosion inhibitor molecules to form high-strength bonds with the metal surface. Combined with the polymethacrylic acid coating layer and surface carboxylated conductive carbon black described in this invention, the synergistic physicochemical properties of the coating layer and carbon black under the action of a micro-electric field drive the microcapsules to migrate directionally to the anode region, thereby achieving local enrichment of the corrosion inhibitor in the anode corrosion zone. Detailed Implementation

[0010] The technical solutions in the embodiments of the present invention will be clearly and completely described below; the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Example 1: This embodiment provides a method for preparing a self-aggregating corrosion inhibitor for oil and gas production and transportation based on heterocyclic substitution, specifically including the following steps: Preparation of S1 heterocyclic corrosion inhibitor molecules: Under nitrogen protection, 10.3 g of diethylenetriamine and 20.0 g of 2-aminothiazole were added to 150 mL of ethanol and stirred to dissolve. Glacial acetic acid was added dropwise to adjust the pH of the system to 4.5. 16.2 g of 37% formaldehyde aqueous solution was slowly added dropwise to the mixture to make the molar ratio of diethylenetriamine to formaldehyde 1:2. The mixture was heated to 70 °C and refluxed for 6 hours. After the reaction, the solvent was removed by rotary evaporation under reduced pressure, washed with deionized water, and dried under vacuum to obtain a heterocyclic corrosion inhibitor molecule. In this molecule, the formaldehyde reacts to form a methylene bridging group, which is connected at both ends to the primary amino group of diethylenetriamine and the amino group of 2-aminothiazole, respectively. The exact connection sites between each fragment were identified. The yield was 88.5% and the purity was 99.2%. A small amount of the product was characterized by infrared spectroscopy and proton nuclear magnetic resonance spectroscopy. The Fourier transform infrared spectrum showed values ​​in the 3400-3200 cm⁻¹ range. -1 A distinct NH stretching vibration peak appears at 1620 cm⁻¹. -1The presence of a C=N stretching vibration peak at 6.8 ppm and 7.2 ppm in the proton NMR spectrum confirms the successful preparation of the heterocyclic corrosion inhibitor molecule. Preparation of S2 responsive mesoporous nanocontainers: 5.0 g of MCM-41 type mesoporous silica with a pore size of 2.5 nm was dispersed in 200 mL of methanol. 6.0 g of heterocyclic corrosion inhibitor molecules obtained in step S1 were pre-dissolved in methanol. The mixture was stirred at room temperature for 24 hours and collected by centrifugation to obtain supported mesoporous silica. Heterocyclic corrosion inhibitor molecules were stored inside the mesopores through physical adsorption, achieving the initial loading of the drug. Separately, ethylenediaminetetraacetic acid dianhydride and 3-aminopropyltriethoxysilane were added to 120 mL of N,N-dimethylformamide in a molar ratio of 1:2.2. The mixture was stirred at 50 °C for 18 hours under nitrogen protection, washed, and vacuum dried to obtain the ethylenediaminetetraacetic acid-silane coupling agent with a yield of 85.2%. A small amount of the product was subjected to infrared spectroscopy. The Fourier transform infrared spectrum showed a value at 1730 cm⁻¹. -1 and 1650cm -1 The presence of characteristic peaks for carboxylic acid carbonyl and amide carbonyl groups at the locations indicated successful synthesis of the coupling agent. The above-mentioned supported mesoporous silica was dispersed in 150 mL of anhydrous toluene, and 5.0 g of ethylenediaminetetraacetic acid-silane coupling agent was added. The mixture was refluxed at 80 °C for 12 hours under nitrogen protection, and centrifuged and washed to obtain grafted mesoporous silica. The ethylenediaminetetraacetic acid-silane coupling agent introduced chelating groups on the surface of the mesoporous silica, providing reaction sites for subsequent metal ion crosslinking and blocking. Grafted mesoporous silica was dispersed in 100 mL of zinc sulfate aqueous solution, with a mass ratio of grafted mesoporous silica to zinc sulfate of 1:2. After stirring for 4 hours, the mixture was centrifuged, washed, and freeze-dried to obtain mesoporous silica nanocontainers with zinc ions crosslinked on the surface, with a yield of 90.3%. The mesopores were sealed by the coordination crosslinking effect of zinc ions and ethylenediaminetetraacetic acid groups, achieving responsive blocking to corrosion inhibitor molecules. Transmission electron microscopy characterization showed that it maintained a highly ordered mesoporous structure without pore collapse. X-ray photoelectron spectroscopy detected obvious Zn2p characteristic peaks, proving that zinc ions were successfully crosslinked and loaded. Assembly of S3 responsive aggregated microcapsules: 3.0g of mesoporous silica nanocapsules with zinc ion crosslinking obtained in step S2 and 1.0g of surface carboxylated conductive carbon black with a particle size of 200nm were ultrasonically dispersed in 80mL of water. 10.0g of methacrylic acid monomer, 0.6g of N,N-methylenebisacrylamide and 0.12g of potassium persulfate were added to form an aqueous dispersion. The aqueous phase was slowly added dropwise to 240 mL of cyclohexane oil phase, which contained 6.0 g of sorbitan monooleate emulsifier. The volume ratio of the aqueous phase to the oil phase was 1:3. A reverse microemulsion was formed by high-speed shearing. After deoxygenation by purging with nitrogen, in-situ free radical polymerization was carried out at 65 °C for 4 hours. After the reaction, the microemulsion was demulsified, centrifuged, washed, and freeze-dried to obtain responsive corrosion inhibitor microcapsules with a polymethacrylic acid coating structure, with a yield of 86.7%. Scanning electron microscopy characterization showed that the microcapsules were regular spherical with an average particle size of 400 nm and obvious polymer coating characteristics on the surface, proving that the responsive aggregated microcapsules were successfully assembled.

[0011] Example 2: This embodiment provides a method for preparing a self-aggregating corrosion inhibitor for oil and gas production and transportation based on heterocyclic substitution, specifically including the following steps: Preparation of S1 heterocyclic corrosion inhibitor molecules: Under nitrogen protection, 10.3 g of diethylenetriamine and 18.0 g of 2-aminothiazole were added to 150 mL of ethanol and stirred to dissolve. Glacial acetic acid was added dropwise to adjust the pH of the system to 4.0. 14.6 g of 37% formaldehyde aqueous solution was slowly added dropwise to the mixture to make the molar ratio of diethylenetriamine to formaldehyde 1:1.8. The mixture was heated to 65 °C and refluxed for 5 hours. After the reaction, the solvent was removed by rotary evaporation under reduced pressure, followed by washing with deionized water and vacuum drying to obtain the heterocyclic corrosion inhibitor molecule with a yield of 86.2% and a purity of 98.8%. The Fourier transform infrared spectrum showed values ​​in the 3400-3200 cm⁻¹ range. -1 The NH stretching vibration peak appears at 1620 cm⁻¹. -1 The presence of a C=N stretching vibration peak and the presence of a proton NMR spectrum showing a thiazole ring proton signal proves that the heterocyclic corrosion inhibitor molecule was successfully prepared. Preparation of S2 responsive mesoporous nanocontainers: 5.0 g of MCM-41 type mesoporous silica with a pore size of 2.2 nm was dispersed in 200 mL of methanol. 2.5 g of heterocyclic corrosion inhibitor molecules obtained in step S1 were pre-dissolved in methanol. The mixture was stirred at room temperature for 20 hours and collected by centrifugation to obtain supported mesoporous silica. The heterocyclic corrosion inhibitor molecules were stored inside the mesopores through physical adsorption, thus achieving the initial loading of corrosion inhibitor molecules. Separately, ethylenediaminetetraacetic acid dianhydride and 3-aminopropyltriethoxysilane were added to 100 mL of N,N-dimethylformamide in a molar ratio of 1:2. The mixture was stirred at 40 °C for 12 hours under nitrogen protection, washed, and vacuum dried to obtain the ethylenediaminetetraacetic acid-silane coupling agent with a yield of 83.6%. The Fourier transform infrared spectrum showed a peak value at 1730 cm⁻¹. -1 and 1650cm -1 The presence of a carbonyl characteristic peak at the point indicates that the coupling agent was successfully synthesized. The above-mentioned supported mesoporous silica was dispersed in 150 mL of anhydrous toluene, and 2.5 g of ethylenediaminetetraacetic acid-silane coupling agent was added. The mixture was refluxed at 75 °C for 10 hours under nitrogen protection, and centrifuged and washed to obtain grafted mesoporous silica. The ethylenediaminetetraacetic acid-silane coupling agent introduced chelating groups on the surface of the mesoporous silica, providing reaction sites for subsequent metal ion crosslinking and blocking. Grafted mesoporous silica was dispersed in 100 mL of zinc sulfate aqueous solution, with a mass ratio of grafted mesoporous silica to zinc sulfate of 1:1. After stirring for 3 hours, the mixture was centrifuged, washed, and freeze-dried to obtain mesoporous silica nanocapsules with zinc ions crosslinked on the surface, with a yield of 89.1%. The mesopores were sealed by the coordination crosslinking effect of zinc ions and ethylenediaminetetraacetic acid groups, achieving responsive blocking of corrosion inhibitor molecules. Transmission electron microscopy characterization showed that the ordered mesoporous structure was maintained, and X-ray photoelectron spectroscopy detected the characteristic peak of Zn2p, proving that zinc ions were successfully crosslinked and loaded. Assembly of S3 responsive aggregated microcapsules: 2.5g of mesoporous silica nanocapsules with zinc ion crosslinking obtained in step S2 and 1.0g of surface carboxylated conductive carbon black with a particle size of 180nm were ultrasonically dispersed in 80mL of water. 10.0g of methacrylic acid monomer, 0.2g of N,N-methylenebisacrylamide and 0.05g of potassium persulfate were added to form an aqueous dispersion. The above aqueous phase was slowly added dropwise to 160mL of cyclohexane oil phase, which contained 4.0g of sorbitan monooleate emulsifier. The volume ratio of the aqueous phase to the oil phase was 1:2. High-speed shearing was used to form a reverse microemulsion. After deoxygenation by purging with nitrogen, in-situ free radical polymerization was carried out at 60°C for 3 hours. After the reaction, the microemulsion was demulsified, centrifuged, washed, and freeze-dried to obtain responsive corrosion inhibitor microcapsules with a yield of 84.5%. Scanning electron microscopy characterization showed that the microcapsules were regular spherical with an average particle size of 380 nm and had a polymer coating layer on the surface, proving that the responsive aggregated microcapsules were successfully assembled.

[0012] Example 3: This embodiment provides a method for preparing a self-aggregating corrosion inhibitor for oil and gas production and transportation based on heterocyclic substitution, specifically including the following steps: Preparation of S1 heterocyclic corrosion inhibitor molecules: Under nitrogen protection, 10.3 g of diethylenetriamine and 22.0 g of 2-aminothiazole were added to 150 mL of ethanol and stirred to dissolve. Glacial acetic acid was added dropwise to adjust the pH of the system to 5.0. 17.8 g of 37% formaldehyde aqueous solution was slowly added dropwise to the mixture to make the molar ratio of diethylenetriamine to formaldehyde 1:2.2. The mixture was heated to 75 °C and refluxed for 7 hours. After the reaction, the solvent was removed by rotary evaporation under reduced pressure, followed by washing with deionized water and vacuum drying to obtain the heterocyclic corrosion inhibitor molecule with a yield of 89.4% and a purity of 99.5%. The Fourier transform infrared spectrum showed values ​​in the 3400-3200 cm⁻¹ range.-1 The NH stretching vibration peak appears at 1620 cm⁻¹. -1 The presence of a C=N stretching vibration peak and the presence of a proton NMR spectrum showing a thiazole ring proton signal proves that the heterocyclic corrosion inhibitor molecule was successfully prepared. Preparation of S2 responsive mesoporous nanocontainers: 5.0 g of MCM-41 type mesoporous silica with a pore size of 2.8 nm was dispersed in 200 mL of methanol. 10.0 g of heterocyclic corrosion inhibitor molecules obtained in step S1 were pre-dissolved in methanol. The mixture was stirred at room temperature for 28 hours and collected by centrifugation to obtain supported mesoporous silica. Heterocyclic corrosion inhibitor molecules were stored inside the mesopores through physical adsorption, achieving the initial loading of the drug. Separately, ethylenediaminetetraacetic acid dianhydride and 3-aminopropyltriethoxysilane were added to 150 mL of N,N-dimethylformamide in a molar ratio of 1:2.5. The mixture was stirred at 60 °C for 24 hours under nitrogen protection, washed, and vacuum dried to obtain the ethylenediaminetetraacetic acid-silane coupling agent with a yield of 86.5%. The Fourier transform infrared spectrum showed a value at 1730 cm⁻¹. -1 and 1650cm -1 The presence of a carbonyl characteristic peak at the point indicates that the coupling agent was successfully synthesized. The above-mentioned supported mesoporous silica was dispersed in 150 mL of anhydrous toluene, and 7.5 g of ethylenediaminetetraacetic acid-silane coupling agent was added. The mixture was refluxed at 85 °C for 14 hours under nitrogen protection, and centrifuged and washed to obtain grafted mesoporous silica. The ethylenediaminetetraacetic acid-silane coupling agent introduced chelating groups on the surface of the mesoporous silica, providing reaction sites for subsequent metal ion crosslinking and blocking. Grafted mesoporous silica was dispersed in 100 mL of zinc sulfate aqueous solution, with a mass ratio of grafted mesoporous silica to zinc sulfate of 1:3. After stirring for 5 hours, the mixture was centrifuged, washed, and freeze-dried to obtain mesoporous silica nanocapsules with zinc ions crosslinked on the surface, with a yield of 91.2%. The mesopores were sealed by the coordination crosslinking effect of zinc ions and ethylenediaminetetraacetic acid groups, achieving responsive blocking of corrosion inhibitor molecules. Transmission electron microscopy characterization showed that the ordered mesoporous structure was maintained, and X-ray photoelectron spectroscopy detected the characteristic peak of Zn2p, proving that zinc ions were successfully crosslinked and loaded. Assembly of S3 responsive aggregated microcapsules: 3.5g of mesoporous silica nanocapsules with zinc ion crosslinking obtained in step S2 and 1.0g of surface carboxylated conductive carbon black with a particle size of 220nm were ultrasonically dispersed in 80mL of water. 10.0g of methacrylic acid monomer, 1.0g of N,N-methylenebisacrylamide and 0.20g of potassium persulfate were added to form an aqueous dispersion. The aqueous phase was slowly added dropwise to 400 mL of cyclohexane oil phase, which contained 10.0 g of sorbitan monooleate emulsifier. The volume ratio of the aqueous phase to the oil phase was 1:5. High-speed shearing was used to form a reverse microemulsion. After deoxygenation by purging with nitrogen, in-situ free radical polymerization was carried out at 70 °C for 5 hours. After the reaction, the microemulsion was demulsified, centrifuged, washed, and freeze-dried to obtain responsive corrosion inhibitor microcapsules with a yield of 87.8%. Scanning electron microscopy characterization showed that the microcapsules were regularly spherical with an average particle size of 420 nm and had a polymer coating layer on the surface, proving that the responsive aggregated microcapsules were successfully assembled.

[0013] Example 4: This embodiment provides a method for preparing a self-aggregating corrosion inhibitor for oil and gas production and transportation based on heterocyclic substitution, specifically including the following steps: Preparation of S1 heterocyclic corrosion inhibitor molecule: Under nitrogen protection, 10.3 g of diethylenetriamine and 19.0 g of 2-aminothiazole were added to 150 mL of ethanol and stirred to dissolve. Glacial acetic acid was added dropwise to adjust the pH of the system to 4.6. 15.4 g of 37% formaldehyde aqueous solution was slowly added dropwise to the mixture to make the molar ratio of diethylenetriamine to formaldehyde 1:1.9. The mixture was heated to 68 °C and refluxed for 6 hours. After the reaction was completed, the solvent was removed by rotary evaporation under reduced pressure, washed with deionized water, and dried under vacuum to obtain the heterocyclic corrosion inhibitor molecule. Preparation of S2 responsive mesoporous nanocontainers: 5.0 g of MCM-41 type mesoporous silica with a pore size of 2.4 nm was dispersed in 200 mL of methanol. 7.5 g of the heterocyclic corrosion inhibitor molecule obtained in step S1 was pre-dissolved in methanol. The mixture was stirred at room temperature for 22 hours, centrifuged, and collected to obtain supported mesoporous silica. Separately, ethylenediaminetetraacetic acid dianhydride and 3-aminopropyltriethoxysilane were added to N,N-dimethylformamide in a molar ratio of 1:2.1. The mixture was stirred at 45 °C for 16 hours under nitrogen protection, washed, and vacuum dried to obtain an ethylenediaminetetraacetic acid-silane coupling agent. The above-mentioned supported mesoporous silica was dispersed in 150 mL of anhydrous toluene, and 4.5 g of ethylenediaminetetraacetic acid-silane coupling agent was added. The mixture was refluxed at 78 °C for 11 hours under nitrogen protection, and centrifuged and washed to obtain grafted mesoporous silica. The grafted mesoporous silica was dispersed in 100 mL of zinc sulfate aqueous solution, wherein the mass ratio of grafted mesoporous silica to zinc sulfate was 1:1.5. The mixture was stirred for 4 hours, centrifuged and washed, and freeze-dried to obtain mesoporous silica nanocontainers with zinc ions crosslinked on the surface. Assembly of S3 responsive aggregated microcapsules: 3.0 g of the nanocapsules obtained in step S2 and 1.0 g of surface carboxylated conductive carbon black with a particle size of 200 nm were ultrasonically dispersed in 80 mL of water. 10.0 g of methacrylic acid monomer, 0.4 g of N,N-methylenebisacrylamide, and 0.10 g of potassium persulfate were added to form an aqueous dispersion. The above aqueous phase was slowly added dropwise to 320 mL of cyclohexane oil phase, which contained 8.0 g of sorbitan monooleate emulsifier. The volume ratio of the aqueous phase to the oil phase was 1:4. High-speed shearing was used to form a reverse microemulsion. After deoxygenation by purging with nitrogen, in-situ free radical polymerization was carried out at 63 °C for 4 hours. After the reaction, the microemulsion was demulsified, centrifuged, washed, and freeze-dried to obtain responsive corrosion inhibitor microcapsules.

[0014] Comparative Example 1: The difference between this comparative example and Example 1 is that 2-aminothiazole is not added in step S1, and only diethylenetriamine is reacted with formaldehyde in an ethanol medium. Other operating steps and process parameters are exactly the same as in Example 1.

[0015] Comparative Example 2: The difference between this comparative example and Example 1 is that the molar ratio of diethylenetriamine to 2-aminothiazole in step S1 is replaced by 1:1.0 instead of 1:2. All other operating steps and process parameters are exactly the same as in Example 1.

[0016] Comparative Example 3: The difference between this comparative example and Example 1 is that the zinc sulfate crosslinking and plugging treatment in step S2 is omitted, that is, the grafted mesoporous silica is directly used in step S3 after washing. Other operating steps and process parameters are exactly the same as in Example 1.

[0017] Comparative Example 4: The difference between this comparative example and Example 1 is that surface carboxylated conductive carbon black is not added in step S3, while the other operating steps and process parameters are exactly the same as in Example 1.

[0018] Comparative Example 5: The difference between this comparative example and Example 1 is that: in step S3, methacrylic acid monomer, N,N-methylenebisacrylamide and potassium persulfate are not added, and in-situ free radical polymerization is not carried out. The nanocontainers obtained in step S2 are physically mixed with surface carboxylated conductive carbon black and dried. Other operation steps and process parameters are exactly the same as in Example 1.

[0019] Performance Tests and Data Sheets: The pore size of the porous silica in the text was determined using the nitrogen adsorption-desorption isotherm; the particle size of the conductive carbon black and microcapsules was determined using the dynamic light scattering test standard; the corrosion weight loss test of the Q235 steel specimen was performed in accordance with GB / T4334-2020; a simulated oil and gas gathering and transportation salt-containing medium with a total mineralization of 30000 mg / L and a pH of 6.5 was used to conduct a corrosion weight loss test on the Q235 steel specimen at 120℃, and the retention of the adsorption film was examined under a flow rate of 3 m / s. The corrosion inhibition efficiency was calculated by the weight loss method; the drug loading was calculated by the mass difference before and after loading the nanocontainer, the release behavior was calculated by the change in the concentration of the corrosion inhibitor in the solution, and the enrichment factor in the anodic region was determined by in-situ fluorescence microscopy to determine the relative enrichment degree. Table 1 Performance test results of each embodiment and comparative example Example 1 318 7.8 81.5 4.8 88.6 96.2 Example 2 285 10.9 74.3 3.9 82.4 92.8 Example 3 301 9.6 78.7 4.2 84.1 93.9 Example 4 309 8.7 79.8 4.4 85.5 94.8 Comparative Example 1 296 8.4 79.5 4.6 56.3 77.4 Comparative Example 2 290 8.5 78.9 4.5 68.2 84.1 Comparative Example 3 317 38.6 42.7 4.7 87.9 82.6 Comparative Example 4 316 8.0 80.8 1.6 87.4 85.9 Comparative Example 5 316 22.4 61.2 2.0 86.9 83.5 As can be seen from the comparison of the test results of Example 1 and Comparative Example 1 in Table 1, the film retention rate and corrosion inhibition efficiency decreased significantly after omitting the heterocyclic substituents. The 2-aminothiazole introduced nitrogen and sulfur heteroatoms and a conjugated structure, which can form stronger coordination adsorption with the iron surface and is also conducive to the parallel arrangement of molecules on the metal surface. If this conjugated structure is not introduced, the molecules mainly rely on amine adsorption, the density and erosion resistance of the surface coating film decrease, and it is easier to desorb under high temperature and flow conditions. Therefore, the film retention rate decreased from 88.6% to 56.3%, and the corrosion inhibition efficiency decreased from 96.2% to 77.4%. As can be seen from the comparison of the test results of Example 1 and Comparative Example 2 in Table 1, reducing the ratio of diethylenetriamine to 2-aminothiazole will decrease the film retention rate and corrosion inhibition efficiency. After the heterocyclic grafting density is reduced, the number of effective coordination sites in the molecule decreases, the synergistic adsorption of Fe-N and Fe-S is weakened, the coverage of the adsorbed film formed on the surface decreases, and the locally exposed metal surface is more likely to come into contact with the corrosive medium. Therefore, the film retention rate drops from 88.6% to 68.2%, and the corrosion inhibition efficiency drops from 96.2% to 84.1%. As can be seen from the comparison of the test results of Example 1 and Comparative Example 3 in Table 1, after omitting the zinc ion crosslinking blockade, the leakage rate of neutral media increased significantly, while the cumulative release rate and corrosion inhibition efficiency in iron-containing media decreased; in Example 1, ethylenediaminetetraacetic acid and Zn²⁺ + This forms a sealing structure, which can limit the premature diffusion of corrosion inhibitors in mesopores in non-corrosive areas and undergo competitive displacement when the iron ion concentration increases, resulting in a more obvious on-demand release characteristic; without Zn²⁺… + In the case of cross-linking and plugging, the mesopores remain open, resulting in significant loss of the corrosion inhibitor before it enters the corrosive zone. This leads to a decrease in the locally available dosage of the inhibitor, causing the leakage rate of the neutral medium to rise from 7.8% to 38.6% within 12 hours, and the corrosion inhibition efficiency to drop to 82.6%. As can be seen from the comparison of the test results of Example 1 and Comparative Example 4 in Table 1, omitting the surface carboxylated conductive carbon black significantly reduced the enrichment factor in the anodic region, leading to a decrease in corrosion inhibition efficiency. In Example 1, the negatively charged conductive carbon black and the nanocapsule together constitute an electrochemical migration enhancement carrier, which can migrate to the anodic region under the action of the corrosion micro-electric field, making the agent concentration at the local corrosion site higher than that of the bulk fluid. Without the addition of conductive components, the microcapsules mainly rely on conventional diffusion distribution, making it difficult to form a high local concentration in the anodic region. Therefore, the enrichment factor in the anodic region decreased from 4.8 to 1.6, and the corrosion inhibition efficiency decreased from 96.2% to 85.9%. As can be seen from the comparison of the test results of Example 1 and Comparative Example 5 in Table 1, omitting the polymethacrylic acid coating layer increases the leakage rate of the neutral medium and decreases the enrichment factor and corrosion inhibition efficiency in the anodic area. The polymethacrylic acid outer layer in Example 1 remains relatively stable under higher pH conditions, and undergoes protonation and contraction condensation in the localized acidification area, which can correspond the carrier exposure process with the acidification phenomenon in the corrosion area. Without this coating layer, it is impossible to achieve precise matching between the carrier exposure and release and the localized acidification microenvironment in the anodic area. Without the polymer coating layer, the carrier is also prone to direct contact with the medium in non-corrosive areas, the agent is released prematurely, and it is impossible to achieve directional deposition and exposure by utilizing localized acidification. Therefore, the leakage rate of the neutral medium after 12 hours increases from 7.8% to 22.4%, the enrichment factor in the anodic area decreases from 4.8 to 2.0, and the corrosion inhibition efficiency decreases to 83.5%. As can be seen from the test results of Examples 1 to 4 in Table 1, when each parameter is within the range defined by the present invention, high corrosion inhibition performance can be obtained. Among them, Example 2 uses the lower limit parameter combination, and the degree of crosslinking, gate strength and heterocyclic grafting are relatively low. Therefore, it is slightly lower than Example 1 in terms of drug loading, release selectivity and film stability. Example 3 uses the upper limit parameter combination. Although its mesopore blocking and surface polymer coating effects are strong, the higher degree of crosslinking will increase the mass transfer resistance. Therefore, its iron ion response release rate and local enrichment effect are lower than those of Example 1. Example 4 uses the intermediate parameter combination. Its comprehensive performance is between that of Example 1 and Examples 2 and 3, which shows that the parameter range of the present invention has feasibility and stability.

[0020] The above are merely specific embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments for application in other fields. However, any conventional modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a self-aggregating corrosion inhibitor for oil and gas production and transportation based on heterocyclic substitution, characterized in that, Includes the following steps: Heterocyclic corrosion inhibitor molecules were prepared by amine-aldehyde condensation reaction of diethylenetriamine, 2-aminothiazole and formaldehyde under acidic conditions, wherein the molar ratio of diethylenetriamine, 2-aminothiazole and formaldehyde was 1:(1.8-2.2):(1.8-2.2). Mesoporous silica nanocontainers with zinc ion crosslinking on their surfaces were prepared using the aforementioned heterocyclic corrosion inhibitor molecules, ethylenediaminetetraacetic acid-silane coupling agent, and zinc salt solution. The nanocontainers and surface carboxylated conductive carbon black were ultrasonically dispersed in an aqueous solution containing methacrylic acid monomer, crosslinking agent, and initiator at a mass ratio of (2.5-3.5):1 to form an aqueous phase. The mass of methacrylic acid monomer was 100 parts, the crosslinking agent was 2-10 parts, the initiator was 0.5-2 parts, and the total mass of the nanocontainers and surface carboxylated conductive carbon black was 35-45 parts. The aqueous phase is added dropwise to the oil phase containing the emulsifier, with a volume ratio of aqueous phase to oil phase of 1:(2-5), and shearing is performed to form a reverse microemulsion; after deoxygenation, the temperature is raised to carry out an in-situ free radical polymerization reaction to form a polymethyl methacrylate coating layer on the surface of the nanocontainer. After the reaction is completed, demulsification, centrifugation washing and freeze drying are performed in sequence to obtain the corrosion inhibitor. The preparation of the mesoporous silica nanocontainer with zinc ions cross-linked on its surface includes the following steps: Step 1: Disperse mesoporous silica in a methanol solution containing heterocyclic corrosion inhibitor molecules, wherein the mass ratio of mesoporous silica to heterocyclic corrosion inhibitor molecules is 1:(0.5-2), stir to carry out physical adsorption loading, and collect by centrifugation to obtain supported mesoporous silica. Step 2: Under nitrogen protection, the supported mesoporous silica is dispersed in anhydrous toluene, and ethylenediaminetetraacetic acid-silane coupling agent is added, wherein the mass ratio of the dried supported mesoporous silica to the ethylenediaminetetraacetic acid-silane coupling agent is 1:(0.5-1.5). The mixture is heated under reflux to complete the surface grafting and obtain grafted mesoporous silica. Step 3: Disperse the grafted mesoporous silica in an aqueous solution containing zinc sulfate, wherein the mass ratio of grafted mesoporous silica to zinc sulfate is 1:(1-3), stir for crosslinking, centrifuge, wash and freeze dry to obtain mesoporous silica nanocontainers with zinc ions crosslinked on the surface. The preparation steps of the ethylenediaminetetraacetic acid-silane coupling agent are as follows: under nitrogen protection, ethylenediaminetetraacetic acid dianhydride and 3-aminopropyltriethoxysilane are added to N,N-dimethylformamide solvent at a molar ratio of 1:(2-2.5), and the mixture is stirred and reacted at 40-60°C for 12-24 hours. After the reaction is completed, the mixture is washed and vacuum dried to obtain the ethylenediaminetetraacetic acid-silane coupling agent.

2. The method for preparing a self-aggregating corrosion inhibitor for oil and gas production and transportation based on heterocyclic substitution according to claim 1, characterized in that, The in-situ free radical polymerization reaction is carried out at a temperature of 60-70℃ for 3-5 hours.

3. The method for preparing a self-aggregating corrosion inhibitor for oil and gas production and transportation based on heterocyclic substitution according to claim 1, characterized in that, The crosslinking agent is N,N-methylenebisacrylamide; the initiator is potassium persulfate; the emulsifier is sorbitan monooleate; and the oil phase is cyclohexane.

4. The method for preparing a self-aggregating corrosion inhibitor for oil and gas production and transportation based on heterocyclic substitution according to claim 1, characterized in that, The mesoporous silica nanocontainer with zinc ions crosslinked on its surface is made of MCM-41 type mesoporous silica with a pore size of 2.2-2.8 nm; the surface carboxylated conductive carbon black has a particle size of 180-220 nm.

Citation Information

Patent Citations

  • Preparation method of magnesium alloy surface micro-arc oxidation corrosion inhibition coating

    CN120797139A

  • Deplating agent for aluminum alloy coating and preparation method of deplating agent

    CN121023516A